Problems of young people on the labour market in Podlaskie province in the opinion of employers - Urszula Kobylinska (Institute of Economic Research (IER), 2017)
In this article, chosen results of the study regarding the opinions of employers in the Podlaskie province (Poland) on their perception of young people entering the labour market are presented. In particular, efforts have been made to answer the following questions: what are the reasons for not recruiting young people and what are the largest competency gaps that employers notice within this group of employees? The unemployment rate of young people in Poland in the age range 15-29, reached 14.2% in 2015. For comparison, at that time the average for the EU was higher by almost two percentage points, and the decline compared to the year 2013 was lower than in Poland. In all provinces in Poland, the unemployment rate in 2015 was in the double-digits, and the Podlaskie province had the worst indicator of all regions with an unemployment rate of 13.8% among youth. It turns out that higher education in Poland has lost its importance in the process of hiring staff. Employers are increasingly less likely to look at the educational background of candidates, as they focus more on their experience and specific skills. The purpose of this article is to present the chosen results of research regarding the diagnosis of the situation of young people on the labour market in the Podlaskie province from the perspective of employers. In particular competency gaps were identified and other reasons for not recruiting young people. this article includes analyses of desk research and results of quantitative research, which was carried out on a sample of 346 respondents among 16 companies registered in the Podlaskie province. Among the reasons for not employing young people which were most often mentioned by the entrepreneurs from the Podlaskie province in quantitative research were financial reasons. During the interviews, employers indicated the reasons for not employing young people such as "lack of appropriate qualifications," "specific skills" or simply "practical preparation for work." Employers when asked about the competence gaps of young people pointed out that they have a lack of experience, initiative and entrepreneurship, as well as learning skills.
Keywords: A11; J21; J23; J58; 330; unemployment; young people; labour market; competency gaps